2018
DOI: 10.1097/wnr.0000000000000973
|View full text |Cite
|
Sign up to set email alerts
|

Tonal and vowel information processing in Chinese spoken word recognition

Abstract: In the present study, the time course of tonal and vowel information processing of the spoken words in Mandarin Chinese was investigated using a delayed-response paradigm. Idiomatic materials, providing semantically highly constraining contexts, were utilized. Besides being presented normally, the terminal monosyllabic words in idioms were manipulated with Tonal, Vowel, or Triple violations (i.e. with consonantal, tonal, and vowel mismatches). Event-related potential results showed that all three violations el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…In a Chinese sentence comprehension task, target words containing rime violations (e.g., 观赚/kuan1 tʂuan4/ "look earn") elicited N400 and P600 of larger amplitudes compared with the congruent condition (e.g., 观众/kuan1 tʂuŋ4/ "audience"), while lexical tone violations (e.g., 观肿/kuan1 tʂuŋ3/ "look swelling") only elicited larger P600, indicating a comparatively later detection of lexical tone violations (Zou et al, 2020). Similar ERP patterns were also observed in the perception of Chinese idioms (Hu et al, 2012;X. Huang et al, 2018) and Chinese classic poems (Li et al, 2014).…”
Section: Lexical Tone and Vowel Perception In Generalsupporting
confidence: 62%
“…In a Chinese sentence comprehension task, target words containing rime violations (e.g., 观赚/kuan1 tʂuan4/ "look earn") elicited N400 and P600 of larger amplitudes compared with the congruent condition (e.g., 观众/kuan1 tʂuŋ4/ "audience"), while lexical tone violations (e.g., 观肿/kuan1 tʂuŋ3/ "look swelling") only elicited larger P600, indicating a comparatively later detection of lexical tone violations (Zou et al, 2020). Similar ERP patterns were also observed in the perception of Chinese idioms (Hu et al, 2012;X. Huang et al, 2018) and Chinese classic poems (Li et al, 2014).…”
Section: Lexical Tone and Vowel Perception In Generalsupporting
confidence: 62%
“…The results showed that the vowel mismatch elicited an earlier negative component and a larger N400 effect than the tone mismatch. This finding suggests that the role of tone is weaker than that of vowels even in constraining idiomatic contexts (Huang et al, 2018).…”
mentioning
confidence: 93%
“…Chinese significantly differs from these languages in that the lexical items have tones. Mandarin Chinese has four different types of lexical tone-namely, high-level, mid-rising, low-dipping, and falling tones (Huang, Liu, Yang, Zhao, & Zhou, 2018;Malins & Joanisse, 2012). One syllable plus different lexical tones can be used to refer to different morphemes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of the patient’s language function in this program may be related to the characteristics of the training material. Chinese idioms are harmonious, with level and oblique deployment and a strong sense of rhythm [ 21 , 22 ]. This rhythm of idioms can be used to prepare for the rapid start of pronunciation by adjusting the speed of pronunciation more clearly similar to Melodic Intonation Therapy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%